FAKTOR-FAKTOR YANG MEMPENGARUHI POLA KONSUMSI SAYURAN PADA RUMAH TANGGA PETANI SAYURAN DI DESA SRIMAHI KECAMATAN TAMBUN UTARA KABUPATEN BEKASI - Azizah Fitria Wijayanti; Trisna Insan Noor (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Vegetables are a food group that contains are vitamins, minerals and other nutrients that needed by the body for health. The quality of vegetable consumption in Indonesia is still low and less diversified, still dominated by food sources of carbohydrates, especially from grains. The Covid-19 pandemic has made people's consumption patterns change from being very consumptive to being reduced. With the spread of the Covid-19 virus, people, especially farmers, are required to maintain their immune system by paying more attention to vegetable consumption. This study aims to determine the factors that influence vegetable consumption in vegetable farmer households. The research was conducted in Srimahi Village, North Tambun District, Bekasi Regency in October-November 2020. The number of research samples was 66 households, with research respondents being housewives. The design used quantitative design with survey method. Data analysis used descriptive statistics with the logistic regression. The results showed that the factors that influenced vegetable consumption in vegetable farmer households were maternal nutritional knowledge, mother's education, and maternal occupation.